Meningkatkan Kapasitas Pelaku Usaha Kerupuk Melalui Pelatihan Usaha Di Desa Bukit Peninjauan Ii Kecamatan Sukaraja Kabupaten Seluma - Nengsih, Mimi Kurnia; Chandra, M. Jeffri Arlinandes; Robiansyah, Anton; Kusuma, Merta; Herfianti, Meiffa (Jurnal Dehasen Untuk Negeri, 2026)
This Community Service Program aims to improve the capacity of cracker entrepreneurs in Bukit Peninjauan II Village, Sukaraja District, Seluma Regency through training in legal matters and business licensing, production management, marketing management, and financial management. The main challenges faced by partners include limited knowledge regarding PIRT (Regional Property Right) permits, inefficient production processes, traditional marketing strategies, and the lack of a financial recording and pricing system based on production costs. The program was implemented in three stages: training on human resource and production management, marketing and business innovation, and training on business licensing and financial management, accompanied by mentoring, monitoring, and evaluation. The results demonstrated a significant increase in participants' understanding and skills, from data-driven production quantity determination, development of innovative marketing strategies, understanding PIRT legality, to the ability to prepare simple bookkeeping and set appropriate selling prices. Overall, this program successfully strengthened the managerial capacity of cracker MSMEs, enabling them to develop their businesses more effectively, efficiently, and sustainably.